2012
DOI: 10.2478/v10247-012-0058-y
|View full text |Cite
|
Sign up to set email alerts
|

Identification of different wheat seeds by electronic nose

Abstract: A b s t r a c t. The potential of electronic nose to distinguish of wheat seeds was studied. The reproducibility and practicability of electronic nose data was evaluated by repeating the analysis of samples with a time difference of two months. The principle components analysis and linear discriminant analysis were applied to the generated patterns to distinguish the varieties of wheat seeds. The results showed that they could distinguish the wheat varieties properly. The stepwise discriminant analysis and a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…An electronic nose is an instrument consisting of an array of electronic and chemical sensors with partial specificity and a pattern recognition system that is capable of recognizing simple or complex odours (Wilson and Baietto, 2009). These devices typically have arrays Anisur Rahman and Byoung-Kwan Cho 288 of sensors used to detect and distinguish odours precisely in complex samples and at low cost (Zhou et al, 2012). Electronic nose devices have been employed in a wide variety of applications, including classification of kernels and microbial pathogen detection.…”
Section: Electronic Nosementioning
confidence: 99%
See 1 more Smart Citation
“…An electronic nose is an instrument consisting of an array of electronic and chemical sensors with partial specificity and a pattern recognition system that is capable of recognizing simple or complex odours (Wilson and Baietto, 2009). These devices typically have arrays Anisur Rahman and Byoung-Kwan Cho 288 of sensors used to detect and distinguish odours precisely in complex samples and at low cost (Zhou et al, 2012). Electronic nose devices have been employed in a wide variety of applications, including classification of kernels and microbial pathogen detection.…”
Section: Electronic Nosementioning
confidence: 99%
“…In addition, machine vision has been shown to exhibit an overall accuracy of greater than 80% in grading maize (Yi et al ., 2007; Wu et al ., 2013) and soybean (Kılıç et al ., 2007). Recently, an electronic nose was used to distinguish among varieties of wheat seeds with an accuracy of 100% (Zhou et al ., 2012). Thermal imaging was used in a recent study to identify eight western Canadian wheat varieties.…”
Section: Quality Detection Of Seeds Using Non-destructive Techniquesmentioning
confidence: 99%
“…Wheat seeds classification using ANN was also estimated whereby the method was found to be effective for recognizing wheat varieties [13]. The study [14] showed that back propagation neural network (BPNN) provided more correct wheat classification at 90% than discriminant analysis which was at 83.33%. Further [15] illustrated how Multi layer perceptron back propagation with image processing algorithm gave higher wheat seeds classification accuracy which was at 95%.…”
Section: Artificial Neural Network (Anns)mentioning
confidence: 99%
“…Depending on the demand of application, viz., detection and/or estimation, analysis has been carried out using various pattern recognition techniques [11], [15]. In published literature, principal component analysis (PCA) and its variants [8]- [14], [15], [16], linear discriminant analysis (LDA) [9]- [11], [14], stepwise discriminant analysis [9], hierarchical cluster analysis [12], [14], average slope multiplication [17], support vector machine (SVM) [18] etc. have been used for the detection of gases delivering different accuracies and success rates.…”
Section: Introductionmentioning
confidence: 99%